Desafíos impuestos por el derecho internacional ambiental al derecho internacional clásico. (2010)
The emergence of international environmental law has produced important challenges to the very foundations of public international law. Traditional concepts such as state sovereignty, subjects of international law, and the early perspectives of national security are being transformed. The needs of the contemporary international society differ from the ones of the Wesphalian conception, situations which clearly explains the raise of alternative views for the understanding of the current dynamics of international law, where concepts like res communis, common concerns and simply “commons” take a privileged place in the study of international law. The foregoing has been strengthened by the international development of the so called erga ommnes obligations, label which is being used by international environmental law as the perfect explanation of its own existence.This academic article presents and studies the abovementioned concepts trying to compare what international law used to be before the emergence of international environmental law and what it is and what it should be in order to attend the developments and challenges imposed by the contemporary international society, particularly by international environmental law, a new fi eld of the corpus juris of public international law.